Co-delivery of rapamycin- and piperine-loaded polymeric nanoparticles for breast cancer treatment - Katiyar, Sameer S.; Muntimadugu, Eameema; Rafeeqi, Towseef Amin; Domb, Abraham J.; Khan, Wahid (Drug delivery, 2016)
P-glycoprotein (P-gp) efflux is the major cause of multidrug resistance (MDR) in tumors when using anticancer drugs, moreover, poor bioavailability of few drugs is also due to P-gp efflux in the gut. Rapamycin (RPM) is in the clinical trials for breast cancer treatment, but its P-gp substrate property leads to poor oral bioavailability and efficacy. The objective of this study is to formulate and evaluate nanoparticles of RPM, along with a chemosensitizer (piperine, PIP) for improved oral bioavailability and efficacy. Poly(d,l-lactide-co-glycolide) (PLGA) was selected as polymer as it has moderate MDR reversal activity, which may provide additional benefits. The nanoprecipitation method was used to prepare PLGA nanoparticles with particle size below 150 nm, loaded with both drugs (RPM and PIP). Prepared nanoparticles showed sustained in vitro drug release for weeks, with initial release kinetics of zero order with non-Fickian transport, subsequently followed by Higuchi kinetics with Fickian diffusion. An everted gut sac method was used to study the effect of P-gp efflux on drug transport. This reveals that the uptake of the RPM (P-gp substrate) has been increased in the presence of chemosensitizer. Pharmacokinetic studies showed better absorption profile of RPM from polymeric nanoparticles compared to its suspension counterpart and improved bioavailability of 4.8-folds in combination with a chemosensitizer. An in vitro cell line study indicates higher efficacy of nanoparticles compared to free drug solution. Results suggest that the use of a combination of PIP with RPM nanoparticles would be a promising approach in the treatment of breast cancer.